Do smoking cessation programmes influence geographical inequalities in health? An evaluation of the impact of the PEGS programme in Christchurch, New Zealand. Issue 5 (25th June 2009) - Hiscock, R; Pearce, J; Barnett, R; Moon, G; Daley, V
Abstract : Objective: To identify the impact of a smoking cessation programme on area-based social and ethnic inequalities in smoking rates through social and ethnic differences in enrolment and quitting. Methods: Analysis of records of 11 325 patients who enrolled in an innovative smoking cessation programme in Christchurch, New Zealand between 2001 and 2006. We compare enrolment, follow-up, quitting and impact on population smoking rates in the most and least deprived neighbourhoods and the neighbourhoods with the lowest and highest proportions of Māori. Results: Enrolment as a proportion of the population was higher from the most deprived areas but as a proportion of neighbourhood smokers, it was lower. Enrolees from the least deprived quintile were 40% more likely to quit than those from the most deprived quintile. Smoking rates were 2.84 (2.75 to 2.93) times higher in the most deprived neighbourhoods. If the programme had not been available we estimate that this differential would have reduced to 2.81 (2.72 to 2.90). In neighbourhoods with the highest proportion of Māori, smoking rates were 2.33 (2.26 to 2.41) times higher and we estimate that without the programme smoking rates would be 2.30 (2.23 to 2.37) times higher. Conclusions: Although enrolees were drawn from a wide variety of backgrounds, those most likely to quit tended to reside in affluent areas or areas with a low proportion of Māori. There was no evidence that this smoking cessation programme increased or decreased inequalities within the Christchurch population. For smoking cessation programmes to have an impact on health inequalities more effort is required in targeting hard-to-reach groups and in encouraging them to quit.